Learning Media Design based on Traditional Game of Tumbu-Tumbu Belanga (T2B) on Salt Hydrolysis Topic - Tangio, Julhim S.; Patilima, Rusmiyati; La Kilo, Jafar; La Kilo, Akram (Universitas Negeri Surabaya, 2021)
This research aimed to test the validity of the feasibility of traditional game learning media on salt hydrolysis. This research was development research (R&D) with a qualitative descriptive approach. This research uses the ADDIE model development design, which consists of 5 (five) stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data collection techniques in this study used a validation sheet for the assessment of the feasibility of tumbu-tumbu learning media. The tumbu-tumbu learning media validation wass assessed by 4 expert validators, namely 2 chemistry lecturers of State University of Gorontalo material experts, 1 media expert lecturer, and 1 high school chemistry teacher. The results of the validation of tumbu-tumbu learning media development obtained an average percentage 0f 89.40%, which was categorized in very feasible criteria. Therefore, the tumbu-tumbu learning media are highly usable in the learning process of salt hydrolysis.